RNA-related DNA damage and repair: The role of N7-methylguanosine in the cell nucleus exposed to UV light - Stixová, Lenka; Tichý, Vlastimil; Bártová, Eva (Heliyon, 2024)
BACKGROUND: Chemical modifications in mRNAs, tRNAs, rRNAs, and non-coding RNAs stabilize these nucleic acids and regulate their function. In addition to regulating the translation of genetic information from mRNA to proteins, it has been revealed that modifications in RNAs regulate repair processes in the genome. METHODS: Using local laser microirradiation, confocal microscopy, dot blots, and mass spectrometry we studied the role of N7-methylguanosine (m7G), which is co-transcriptionally installed in RNA. RESULTS: Here, we show that after UVC and UVA irradiation, the level of m7G RNA is increased initially in the cytoplasm, and after local laser microirradiation, m7G RNA is highly abundant in UVA-damaged chromatin. This process is poly(ADP-ribose) polymerase (PARP)-dependent, but not accompanied by changes in the level of m7G-writers, including methyltransferases RNMT, METTL1, and WBSCR22. We also observed that METTL1 deficiency does not affect the recruitment of m7G RNA to microirradiated chromatin. Analyzing the levels of mRNA, let-7e, and miR-203a in both the cytoplasm and the cell nucleus, we revealed that UVC irradiation changed the level of mRNA, and significantly increased the pool of both let-7e and miR-203a, which correlated with radiation-induced m7G RNA increase in the cytoplasm. CONCLUSIONS: Irradiation by UV light increases the m7G RNA pool in the cytoplasm and in the microirradiated genome. Thus, epigenetically modified RNAslikely contribute to DNA damage responses or m7G signals the presence of RNA damage.